Impact of chemoprophylaxis immunisation under halofantrine (CPS-HF) drug cover in Plasmodium yoelii Swiss mice malaria model - Siddiqui, Arif Jamal; Bhardwaj, Jyoti; Hamadou, Walid Sabri; Goyal, Manish; Jahan, Sadaf; Ashraf, Syed Amir; Jamal, Arshad; Sharma, Pankaj; Sachidanandan, Manojkumar; Badraoui, Riadh; Snoussi, Mejdi; Adnan, Mohd (Folia parasitologica, 2022)
In the present study, we have investigated the role of antimalarial drug halofantrine (HF) in inducing the sterile protection against challenges with sporozoites of the live infectious Plasmodium yoelii (Killick-Kendrick, 1967) in Swiss mice malaria model. We observed that during the first to third sequential sporozoite inoculation cycles, blood-stage patency remains the same in the control and chemoprophylaxis under HF drug cover (CPS-HF) groups. However, a delayed blood-stage infection was observed during the fourth and fifth sporozoite challenges and complete sterile protection was produced following the sixth sporozoite challenge in CPS-HF mice. We also noticed a steady decline in liver stage parasite load after 3th to 6th sporozoite challenge cycle in CPS-HF mice. CPS-HF immunisation results in a significant up-regulation of pro-inflammatory cytokines (IFN-γ, TNF-α, IL-12 and iNOS) and down-regulation of anti-inflammatory cytokines (IL-10 and TGF-β) mRNA expression in hepatic mononuclear cells (HMNC) and spleen cells in the immunised CPS-HF mice (after 6th sporozoite challenge) compared to control. Overall, our study suggests that the repetitive sporozoite inoculation under HF drug treatment develops a strong immune response that confers protection against subsequent challenges with sporozoites of P. yoelii.
Keywords: CPS-immunisation; imunizace; malárie; léčivé přípravky; Pharmaceutical Preparations; myši inbrední BALB C; mRNA expression; zvířata; myši; chemoprofylaxe; Chemoprevention; sporozoites; Mice; Plasmodium yoelii; Malaria; cytokines; Real Time PCR; Animals; Phenanthrenes; fenantreny; Mice, Inbred BALB C; Immunization